The attack on world poverty - Shonfield, Andrew (London : Chatto and Windus, 1961)
This book is on fashion in economic development and the book try to look at it as lack of education as the key factor
Includes bibliographical references.
oo 23/08/2018
Loans
Keywords: Economic assistance; Technical assistance; Developing countries